PENGEMBANGAN LKS DENGAN PENDEKATAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING SISWA SMP (UPEJ Unnes Physics Education Journal, 2015)
AbstrakTujuan  dari  penelitian  ini  adalah  mendapatkan  LKS  dengan  pendekatan  project  based learning,  mengetahui  tingkat  kelayakan  dan  mengetahui  peningkatan  kemampuan problem  solving.  Metode  dalam  penelitian  ini  adalah  R&D  (Research  and  Development). Prosedur penelitian meliputi: (1) studi pendahuluan, (2) studi pengembangan, dan (3) studi  pengujian  produk.  Hasil  uji  kelayakan  menunjukan  bahwa  LKS  dengan pendekatan  project  based  learning  sangat  layak  digunakan  dalam  pembelajaran.  LKS pendekatan  project based learning  dapat meningkatkan kemampuan  problem solving  siswa pada materi cermin. Peningkatan problem solving berada pada kategori sedang. AbstractThe purpose of this study is to obtain worksheets that based on project based learning approach, determine the feasibility and knowing the increase problem solving. Th e method in this study is an R & D (Research and Development). The study procedures include: (1) introduction, (2) design, (3) the development or testing of the product. The test results of the feasibility showed that worksheet is very suitable to be used as a means of physics learning. The result of the study shows that student’s worksheet which are based on project based learning can develop  student’s  problem  solving  skill  in  mirror  materi.  The  level  of  development  of  problem  solving  is adequate.